2009
DOI: 10.1093/alcalc/agn124
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assessment of Drinking on the Internet--3-, 6- and 12-Month Follow-Ups

Abstract: The results are in line with previous studies with mostly shorter follow-up periods suggesting that Internet-based self-assessment services can be useful tools in reducing excessive drinking. A randomized controlled trial would, however, increase our certainty about the causes of the observed changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 16 publications
4
13
0
1
Order By: Relevance
“…The stability of decreased alcohol consumption and alcohol-related problems for up to 6 months is also consistent with findings from previous studies [18,43,44]. One study has shown increases in scores on such outcome measures after 6 months [19], something that we did not see in this study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The stability of decreased alcohol consumption and alcohol-related problems for up to 6 months is also consistent with findings from previous studies [18,43,44]. One study has shown increases in scores on such outcome measures after 6 months [19], something that we did not see in this study.…”
Section: Discussionsupporting
confidence: 93%
“…The finding of a short-term decrease in alcohol consumption and alcohol-related problems, noted at the 3-month follow-up, is consistent with previous research on Web-based interventions for problematic alcohol use [18,25,28,43,44,45]. The stability of decreased alcohol consumption and alcohol-related problems for up to 6 months is also consistent with findings from previous studies [18,43,44].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies suggest that underreporters are more likely to estimate low intake of foods perceived as unhealthy or undesirable (eg, sweets, fats, and snacks) than those perceived as healthy (eg, fruits, vegetables, and reduced fat products) [30,33,34]. Some of the characteristics of e-EPIDEMIOLOGY, such as asynchrony [35-38] and the ease with which privacy can be maintained [39], have made it possible to collect data anonymously on the Internet. This factor could contribute to reducing the problem of underestimation, mainly with those foods/drinks that are socially considered unhealthy, as this would minimize the effect of the psychological factors previously mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation of this study is the possible rate of nonresponse. Some of the characteristics of these types of mobile technologies, such as asynchrony [35-38], the ease with which privacy can be maintained [39], and the light workload for the participants (1 minute per day), helped to increase participation and could have contributed to the minimization of nonresponse rates. Young people have expressed their preference for methods of dietary intake evaluation that utilize new technologies, as they can easily be incorporated into their lifestyles, and are more amenable than traditional paper-based methods [9,17].…”
Section: Discussionmentioning
confidence: 99%
“…Some of the characteristics of these types of mobile technologies, such as asynchrony (36)(37)(38)(39), the ease with which privacy can be maintained (40), as well as the light workload for the participants (one minute per day), helped to increase participation. In addition, the recording of foods/drinks intake was to be completed during 28 consecutive days using the application and at the end of this period using the short paper FFQ, minimizing the likelihood of changes in dietary intake.…”
Section: Strengths and Limitationsmentioning
confidence: 99%